PENGARUH FILTRAT UMBI GADUNG, DAUN SIRSAK DAN HERBA ANTING-ANTING TERHADAP MORTALITAS LARVA SPODOPTERA LITURA - UTAMI NINGSIH, TRI Utami (LenteraBio: Berkala Ilmiah Biologi, 2013)
Spodoptera litura has polifagous quality, or a wide hoste range, which can potentially become pest in various types of food corps, vegetables, and fruits. The use of botanical pesticide environmentally can be used as one way of controlling pest S. litura. This research aimed to know the effect of filtrate Dioscorea hispida, Annona muricata, and Acalypha indica on the mortality of S. litura. This research method used one way analysis of variance (ANOVA), that is the combination of botanical pesticides filtrate. Such as the combination of the filtrate 150 grams Dioscorea hispida; 150 grams of Annona muricata; 150 grams of Acalypha indica; 75 grams of Dioscorea hispida + 75 grams of Annona muricata; 75 grams of Dioscorea hispida + 75 grams of Acalypha indica; 75 grams Annona muricata + 75 grams of Acalypha indica; 50 grams of Dioscorea hispida + 50 grams of Annona muricata + 50 gram of Acalypha indica. This research was conducted in three replications, each replication used 10 Instar larvae 2 from S. litura. The parameter which was observed was the mortality of larvae S. litura, then analyzed by ANOVA. The research result could be seen that the use of combination botanical pesticide was more influential than the giving of single botanical pesticide.